Natural Products among Brown Algae: The Case of Cystoseira schiffneri Hamel (Sargassaceae, Phaeophyceae). Issue 4 (20th March 2017) - Salem, Abdelkader Ben; Di Giuseppe, Graziano; Anesi, Andrea; Hammami, Saoussen; Mighri, Zine; Guella, Graziano
Abstract : A chemotaxonomic study on the marine brown alga Cystoseira schiffneri collected from the Tunisian marine coast allowed us to identify kjellmanianone (1 ) and a new isololiolide derivative named schiffnerilolide (2 ). The structure elucidation and the assignment of relative configurations of the isolated natural products were based on advanced mass spectrometric and nuclear magnetic resonance techniques. This outcome suggested a close phylogenetic relationship of C. schiffneri with brown algae belonging to genus Sargassum C.Agardh . Molecular characterization using the nuclear small subunit rRNA (SSU rRNA) gene (18S) sequence as genetic marker was made. Pigment analysis showed a significant seasonal change of carotenoids, in particular of fucoxanthin and fucoxanthinol. Also galactolipids, the main constituents of the thylakoid membranes, showed remarkable seasonal changes. Abstract :